Improve Critical Thinking Ability and Motivation in Learning Mathematics Through the Adobe Flash Cs 5.0 Game - Fathoni, Fathoni; Amin, Siti Maghfirotun; Khabibah, Siti (International Journal for Educational and Vocational Studies, 2019)
Mathematical learning needs to be given to all students starting from elementary school, so that students practice how to think in drawing conclusions and be able to express their opinions with the beliefs and honesty that comes from someone. But when learning mathematics the problem that often arises is a lack of motivation. Baroody (1993) says that reasoning is an important tool in learning mathematics to produce ideas so students can understand mathematical concepts correctly. Efforts made by teachers to improve thinking skills and motivation in learning mathematics are through the Adobe Flash CS 5.0 game which is expected to provide new and enjoyable experiences for teachers and students. In addition to more varied learning, students can be motivated to learn and enjoy what they learn.